A multiscale stratigraphic investigation of the context of StW 573 'Little Foot' and Member 2, Sterkfontein Caves, South Africa. Issue 133 (August 2019) - Bruxelles, Laurent; Stratford, Dominic J.; Maire, Richard; Pickering, Travis R.; Heaton, Jason L.; Beaudet, Amelie; Kuman, Kathleen; Crompton, Robin; Carlson, Kris J.; Jashashvili, Tea; McClymont, Juliet; Leader, George M.; et al.
Abstract: The Sterkfontein Caves is currently the world's richest Australopithecus -bearing site. Included in Sterkfontein's hominin assemblage is StW 573 ('Little Foot'), a near-complete Australopithecus skeleton discovered in Member 2 in the Silberberg Grotto. Because of its importance to the fossil hominin record, the geological age of StW 573 has been the subject of significant debate. Three main hypotheses have been proposed regarding the formation and age of Member 2 and by association StW 573. The first proposes that Member 2 (as originally defined in the type section in the Silberberg Grotto) started to accumulate at around 2.58 Ma and that the unit is contained within the Silberberg Grotto. The second proposes that Member 2 started forming before 3.67 ± 0.16 Ma and that the deposit extends into the Milner Hall and close to the base of the cave system. The third proposes a 'two-stage burial scenario', in which some sediments and StW 573 represent a secondary and mixed-age accumulation reworked from a higher cave. The stratigraphic and sedimentological implications of these hypotheses are tested here through the application of a multiscale investigation of Member 2, with reference to the taphonomy of the StW 573 skeleton. The complete infilling sequence of Member 2 is described across all exposures of the deposit in the Silberberg Grotto and into the Milner Hall. Sediments are generally stratified and conformably deposited in a sequence of silty sands eroded from well-developed lateritic soils on the landscape surface. Voids, clasts and bioclasts are organized consistently across and through Member 2 conforming with the underlying deposit geometry, indicating gradual deposit accretion with no distinct collapse facies evident and only localized intra-unit postdepositional modification. The stratigraphy and sedimentology of Member 2 support a simple single-stage accumulation process of Member 2 and a primary association between the sediments of Member 2 and the StW 573 'Little Foot' skeleton.